Survival of dogs with myxomatous mitral valve disease administered preclinical pimobendan in comparison to pimobendan-naïve dogs from the onset of congestive heart failure - G. McAulay; M. Hills; J. Dukes-McEwan; E. Dutton; A. Jakubczak; D. Singleton; E. Bode; W. Yangwanitset; M. Hezzell (Journal of Veterinary Cardiology, 2026)

Surviving the Squeeze: Genomic Analysis of a Successful Invasion by European Common Wall Lizards ( Podarcis muralis ) in North America (Ohio, USA ) - Emily R. Bode; Andrew J. Mason; Peri E. Bolton; Ken Petren; Eric J. Gangloff; H. Lisle Gibbs (Molecular Ecology, 2026)
Invasive species that undergo a founder event may experience a decline in genetic diversity yet still establish successful populations. A possible example is a population of the common wall lizard ( Podarcis muralis ) in Cincinnati, Ohio, USA, which was founded following an introduction in the 1950s of a small number of individuals from Europe. We used whole genome sequences of individuals from source and introduced populations to assess the origin, demographic history, population structure, and possible signatures of adaptation in this successful lizard introduction. We first confirmed that the introduced lizards in Ohio are Podarcis muralis using phylogenetic analysis. Patterns of genetic diversity indicate introduced lizards in Cincinnati went through a short‐term bottleneck with increased inbreeding but then rapidly increased in population size, thus minimising losses in genetic diversity. Comparisons of genomic variation between source and introduced populations demonstrate that populations in Cincinnati represent a subset of source genetic variation and show minimal losses of overall genetic diversity. Comparisons of mutation load between source and introduced populations reveal only small increases in load in introduced populations. Finally, tests for selection on the basis of outlier analyses detect targets for potential positive selection in multiple regions of the genome of introduced individuals, suggesting possible adaptation to a novel environment. Overall, we suggest that rapid population growth and possible adaptation have allowed the founding population of introduced lizards to evade the potential negative genetic impacts of small population size and successfully colonise a novel environment.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Pacemaker-lead-associated thrombosis in dogs: a multicenter retrospective study - C. McGrath; A. Dixon; C. Hirst; E.F. Bode; T. DeFrancesco; R. Fries; S. Gordon; D. Hogan; Y. Martinez Pereira; E. Mederska; S. Ostenkamp; K.T. Sykes; et al. (Journal of Veterinary Cardiology, 2023)

Differences in Left Ventricular Enlargement Secondary to Chronic Volume Loading Between English Springer Spaniels and Two Similar Sporting Breeds - D. Dickson; E. Bode; C. Linney; E. Dutton; D. Caivano; T. Bispo; J. Harris; M. Rishniw (Journal of Veterinary Cardiology, 2023)

Comparative pathology of VIC01 isolate and Omicron variant of SARS-CoV-2 infection, including a rechallenge model, in the Golden Syrian hamster - E. Rayner; K. Ryan; Y. Hall; L. Hunter; C. Kennard; J. Edun Hughes; J. Salguero Bodes (Journal of Comparative Pathology, 2023)

The lateral transport of zooplankton explains trophic and taxonomic similarities over the zonal gradient of central Chile - Carolina E. González; Antonio Bode; Igor Fernández-Urruzola; Pamela Hidalgo; Vera Oerder; Rubén Escribano (Journal of Marine Systems, 2023)

Case–Case Comparison of Candida auris Versus Other Candida Species Bloodstream Infections: Results of an Outbreak Investigation in Colombia - Diego H. Caceres; Sandra M. Rivera; Paige A. Armstrong; Patricia Escandon; Nancy A. Chow; Maria Victoria Ovalle; Jorge Díaz; Gordana Derado; Soraya Salcedo; Indira Berrio; Andres Espinosa-Bode; Carmen Varón; et al. (Mycopathologia, 2020)

Zooplankton Taxonomic and Trophic Community Structure Across Biogeochemical Regions in the Eastern South Pacific - Carolina E. González; Rubén Escribano; Antonio Bode; Wolfgang Schneider (Frontiers in Marine Science, 2019)

A systematic review and meta-analysis on Staphylococcus aureus carriage in psoriasis, acne and rosacea - J. E. E. Totté; W. T. van der Feltz; L. G. M. Bode; A. van Belkum; E. J. van Zuuren; S. G. M. A. Pasmans (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Assisting vascular access surgery planning for hemodialysis by using MR, image segmentation techniques, and computer simulations - M. A. G. Merkx; A. S. Bode; W. Huberts; J. Oliván Bescós; J. H. M. Tordoir; M. Breeuwer; F. N. van de Vosse; E. M. H. Bosboom (Medical & Biological Engineering & Computing, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Pathologic progression of mammary carcinomas in a C3(1)/SV40 T/t-antigen transgenic rat model of human triple-negative and Her2-positive breast cancer - M. J. Hoenerhoff; M. A. Shibata; A. Bode; J. E. Green (Transgenic Research, 2011)

Oral Cancer Preventive Practices of South Carolina Dentists and Physicians - Susan G. Reed; Kathleen B. Cartmell; Nadia G. Duffy; Amy E. Wahlquist; Debajyoti Sinha; Amanda Hollinger; Ashley Bode; Anthony J. Alberg; Terry A. Day (Journal of Cancer Education, 2010)

Piperacillin-tazobactam in pediatric cancer patients younger than 25 months: a retrospective multicenter survey - A. Simon; T. Lehrnbecher; U. Bode; A. H. Groll; L. Tramsen; R. Wieland; E. Molitor; G. Fleischhack; H. J. Laws (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

The Impact of Tick Control on the Productivity of Indigenous Cattle under Ranch Conditions in Uganda - J. Okello-Onen; E.M. Tukahirwa; B.D. Perry; G.J. Rowlands; S.N. Nagda; G. Musisi; E. Bode; R. Heinonen; W. Mwayi; J. Opuda-Asibo (Tropical Animal Health and Production, 2003)

Population dynamics of ticks on indigenous cattle in a pastoral dry to semi-arid rangeland zone of Uganda - J. Okello-Onen; E.M. Tukahirwa; B.D. Perry; G.J. Rowlands; S.M. Nagda; G. Musisi; E. Bode; R. Heinonen; W. Mwayi; J. Opuda-Asibo (Experimental and Applied Acarology, 1999)

Nitrate storage by phytoplankton in a coastal upwelling environment - A. Bode; J. A. Botas; E. Fernández (Marine Biology, 1997)

ent -Kaurene synthase is located in proplastids of meristematic shoot tissues - Helmut Aach; Heike Bode; David G. Robinson; Jan E. Graebe (Planta, 1997)

The second case of a t(17;22) in a family with neurofibromatosis type 1: sequence analysis of the breakpoint regions - H. Kehrer-Sawatzki; Jürgen Häussler; Winfrid Krone; Harald Bode; Dieter E. Jenne; Karl U. Mehnert; Ulrich Tümmers; Günter Assum (Human Genetics, 1997)

Presence of antibodies reacting with porcine circovirus in sera of humans, mice, and cattle - I. Tischer; L. Bode; J. Apodaca; H. Timm; D. Peters; R. Rasch; S. Pociuli; E. Gerike (Archives of Virology, 1995)

Zur Betrachtung von Virussymptomen im ultravioletten Licht - Ruth Eicke; Otto Bode; E. Khler (Archives of Virology, 1947)